2018
DOI: 10.1002/jlcr.3594
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and evaluation of an 18F‐labeled trifluoroborate derivative of 2‐nitroimidazole for imaging tumor hypoxia with positron emission tomography

Abstract: 2-Nitroimidazole-based hypoxia imaging tracers such as F-FMISO are normally imaged at late time points (several hours post-injection) due to their slow clearance from background tissues. Here, we investigated if a hydrophilic zwitterion-based ammoniomethyl-trifluoroborate derivative of 2-nitroimidazole, F-AmBF -Bu-2NI, could have the potential to image tumor hypoxia at earlier time points. AmBF -Bu-2NI was prepared in 4 steps. F labeling was conducted via F- F isotope exchange reaction, and F-AmBF -Bu-2NI was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…18F-FMISO is the most widely used tracer but is found at a relatively low concentration in tumors. Moreover, it is normally imaged several hours post-injection, due to its slow clearance from background tissues [358][359][360]. These circumstances could render the image acquisition challenging.…”
Section: Techniques To Map Hypoxic Areas and Immune Infiltrationmentioning
confidence: 99%
“…18F-FMISO is the most widely used tracer but is found at a relatively low concentration in tumors. Moreover, it is normally imaged several hours post-injection, due to its slow clearance from background tissues [358][359][360]. These circumstances could render the image acquisition challenging.…”
Section: Techniques To Map Hypoxic Areas and Immune Infiltrationmentioning
confidence: 99%
“…This approach was previously used for radiolabeling peptides using high activities of [ 18 F]F − and very low amounts of precursor (75-100 nmol), within 30 min with a radiochemical purity >99%, a high molar activity (68-148 GBq/µmol), a radiochemical yield of 20-28%, with HPLC-free purification [34,38,53]. Small [ 18 F]AMBF 3 -conjugated molecules were also synthesized with a radiochemical yield of 14.8 ± 0.4% with a molar activity of 24.5 ± 5.2 GBq/µmol and radiochemical purity >99% [54]. Taking into account that the reaction medium is acid, a significant amount of [ 18 F]F − is lost by volatilization as [ 18 F]hydrogen fluoride during the labeling reaction under vacuum and heating.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro cellular uptake study of radiot in MCF-7 cells under hypoxic and normoxic conditions indicated that th pounds showed no significant difference in cellular uptake under hypox conditions; thus, [ 18 F]1a-c had less selectivity toward hypoxia cells [ 18 F]FMISO. F]4) for ima poxia (Figure 5) [131]. [ 18 F]4 had a logp value of −1.52 ± 0.02 and remained plasma for 1 h. At 1 h p.i., the in vivo biodistribution of [ 18 F]4 in mice with demonstrated minimal uptake in the tumor (0.54 ± 0.13%ID/g), leading t tumor/muscle and tumor/blood ratios (0.51 ± 0.25 and 0.99 ± 0.32, respectiv the tumor uptake was reduced to 0.19 ± 0.04%ID/g, whereas tumor/m mor/blood ratios increased (0.92 ± 0.08 and 2.62 ± 1.02, respectively).…”
Section: F Radiotracers With Linkers For Hypoxiamentioning
confidence: 99%
“…An in vitro cellular uptake study of radiotracers [ 18 F]1a-c in MCF-7 cells under hypoxic and normoxic conditions indicated that these three compounds showed no significant difference in cellular uptake under hypoxic and aerobic conditions; thus, [ 18 F]1a-c had less selectivity toward hypoxia cells compared to [ 18 F]FMISO. Lin and co-workers developed 18 F-labeled zwitterion-based ammoniomethyl-trifluoroborate bearing 2-nitroimidazole ( 18 F-AmBF3-Bu-2NI, [ 18 F]4) for imaging tumor hypoxia (Figure 5) [131]. [ 18 F]4 had a logp value of −1.52 ± 0.02 and remained intact in mouse plasma for 1 h. At 1 h p.i., the in vivo biodistribution of [ 18 F]4 in mice with HT-29 tumors demonstrated minimal uptake in the tumor (0.54 ± 0.13%ID/g), leading to low ratios of tumor/muscle and tumor/blood ratios (0.51 ± 0.25 and 0.99 ± 0.32, respectively).…”
Section: F Radiotracers With Linkers For Hypoxiamentioning
confidence: 99%